(untitled) (Tạp chí Y học Cộng đồng, 2026)
HMG-CoA reductase (3-hydroxy-3-methyl-glutaryl-coenzyme A reductase) is the key enzyme in the mevalonate pathway that governs cholesterol biosynthesis. Inhibition of HMG-CoA reductase effectively reduces hepatic cholesterol production. While synthetic statins are widely prescribed for hypercholesterolemia, their adverse effects highlight the need for natural, plant-derived HMG-CoA reductase inhibitors. Certain natural anti-inflammatory compounds, including polyphenols, flavonoids, and plant extracts, have been reported to inhibit HMG-CoA reductase, thereby suppressing cholesterol biosynthesis (Chaudhary et al., 2023). Curcuma rangjued, commonly known as Scorpion Turmeric (Hue et al., 2024), is traditionally recognized for its potent anti-inflammatory properties, yet it remains underexplored scientifically. Building on prior evidence that the n-hexane fraction of C. rangjued rhizomes exhibits significant anti-inflammatory activity (Hue et al., 2024), we applied a green extraction method to isolate bioactive constituents from fresh rhizomes, designated as GERC7. The inhibitory potential of GERC7 against HMG-CoA reductase was evaluated following the protocol described by Cho et al. (2024). Gas chromatography–mass spectrometry (GC–MS) analysis revealed that GERC7 primarily contains curcumenol, germacrone, and isocurcumenol, all recognized as potent anti-inflammatory sesquiterpenes (Gushiken et al., 2022). GERC7 demonstrated significant inhibition of HMG-CoA reductase activity, with an IC₅₀ value of 58.12 ± 2.14 µg/mL, showing a statistically significant difference compared to the inhibitor-free control (p < 0.05). These results suggest that C. rangjued represents a promising medicinal resource with potential to reduce endogenous cholesterol synthesis and, consequently, the risk of atherosclerosis. Further in vivo studies are warranted to confirm its therapeutic potential as an alternative approach for managing hypercholesterolemia and related cardiovascular diseases.